Common Fixed Points via λ-Sequences in G-Metric Spaces - Yaé Ulrich Gaba (Journal of Mathematics)
We use λ-sequences in this article to derive common fixed points for a family of self-mappings defined on a complete G-metric space. We imitate some existing techniques in our proofs and show that the tools employed can be used at a larger scale. These results generalize well known results in the literature.